Financial Feasibility Analysis of Self-Owned Pattern Printed Kain as Product Innovation Strategy in Fashion Business: A Case Study of Tanair - Gloria Galore Puandhia Sinaga; Atika Irawan (Integrasi Sains Media, 2024)
Generation Z in Indonesia faces a challenge in establishing a strong national identity, underscoring the importance of fostering pride and appreciation for local culture (Manurung et al., 2022). Fashion is a significant avenue for self-expression and can be crucial in cultural promotion. The burgeoning fashion market in Indonesia presents substantial opportunities for businesses aiming to leverage cultural pride. Tanair, a new fashion brand founded in Bandung in 2024, seeks to enhance Indonesian pride through its innovative use of kain (traditional fabric). To navigate the competitive fashion landscape, Tanair requires a comprehensive financial feasibility study to validate its product innovation strategy. This study encompasses a five-year financial projection across three distinct scenarios—pessimistic, baseline, and optimistic—to evaluate Tanair's business plan's financial viability. The analysis reveals positive outcomes across all scenarios, with the pessimistic case demonstrating a payback period of 3.37 years, a net present value (NPV) of Rp61,807,419, a profitability index of 2.5, and an internal rate of return (IRR) of 29%. Notably, the IRR exceeds the weighted average cost of capital (WACC) of 8.92%, indicating a favourable financial outlook for the company. This study confirms that Tanair's innovative approach is financially feasible, positioning it for success in promoting Indonesian cultural heritage through fashion.